Deposition of Inhaled Levofloxacin in Cystic Fibrosis Lungs Assessed by Functional Respiratory Imaging - Carsten Schwarz; Claudio Procaccianti; Benjamin Mignot; Hosein Sadafi; Nicolas Schwenck; Xabier Murgia; Federico Bianco (MDPI AG, 2021)
Pulmonary infections caused by Pseudomonas aeruginosa (PA) represent the leading cause of pulmonary morbidity in adults with cystic fibrosis (CF). In addition to tobramycin, colistin, and aztreonam, levofloxacin has been approved in Europe to treat PA infections. Nevertheless, no lung deposition data on inhaled levofloxacin are yet available. We conducted a Functional Respiratory Imaging (FRI) study to predict the lung deposition of levofloxacin in the lungs of patients with CF. Three-dimensional airway models were digitally reconstructed from twenty high-resolution computed tomography scans obtained from historical patients' records. Levofloxacin aerosols generated with the corresponding approved nebuliser were characterised according to pharmacopeia. The obtained data were used to inform a computational fluid dynamics simulation of levofloxacin lung deposition using breathing patterns averaged from actual CF patients' spirometry data. Levofloxacin deposition in the lung periphery was significantly reduced by breathing patterns with low inspiratory times and high inspiratory flow rates. The intrathoracic levofloxacin deposition percentages for moderate and mild CF lungs were, respectively, 37.0% ± 13.6 and 39.5% ± 12.9 of the nominal dose. A significant albeit modest correlation was found between the central-to-peripheral deposition (C/P) ratio of levofloxacin and FEV1. FRI analysis also detected structural differences between mild and moderate CF airways. FRI revealed a significant intrathoracic deposition of levofloxacin aerosols, which distributed preferentially to the lower lung lobes, with an influence of the deterioration of FEV1 on the C/P ratio. The three-dimensional rendering of CF airways also detected structural differences between the airways of patients with mild and moderate CF.